Therapeutic plasma exchange for hypertriglyceridemia induced acut pancreatitis: the 33 cases experience from a tertiary reference center in Turkey - Kandemir, Altay; Coşkun, Adil; Yavaşoğlu, İrfan and Bolaman, Zahit and Ünübol, Mustafa and Yaşa, Mehmet Hadi and Kadıköylü, Gürhan (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Hypertriglyceridemia (HTG) is the third most common cause of acute pancreatitis. In patients with severe HTG (TG level>1000 mg/dL), it may be beneficial to immediately lower the levels of triglyceride (TG) and chylomicrons. In this study, we present one of the largest case series on the use of therapeutic plasma exchange (TPE) for hypertriglyceridemia-induced acute pancreatitis (HTG-AP). Materials and Methods: Overall, 33 patients who were admitted to our clinic for HTG-AP and underwent TPE between January 2007 and July 2017 were included in the study. Clinical data and outcomes and the reduction of triglyceride levels were examined retrospectively. Results: The TG level decreased by 54.4%, and the total cholesterol level decreased by 52.1% after one TPE session. The TG decrease after the second TPE session was found to be 79.4%. There were 20 (60.6%) patients with mild acute pancreatitis, 10 (30.3%) patients with moderetaly severe acute pancreatitis, and 3 (9.1%) patients with severe acute pancreatitis based on the categorization according to the revised Atlanta criteria. Regarding local complications, the acute peripancreatic fluid collection was observed in 13 (39.4%) patients, acute necrotic collection was observed in 1 (3%) patient, walled-off necrosis was observed in 1 (3%) patient, and pancreatic pseudocyst was not observed in any patient. Mortality was not determined in patients with mild and moderately severe acute pancreatitis, and its rate was 33.3% in patients with severe acute pancreatitis. The overall mortality rate was 3%. No significant complications related to TPE were noted. Conclusion: TPE is a safe and helpful therapeutic treatment method for patients with HTG-AP and may be considered particularly in patients with severe acute pancreatitis. Cite this article as: Kandemir A, Coşkun A, Yavaşoğlu İ, et al. Therapeutic plasma exchange for hypertriglyceridemia induced acut pancreatitis: the 33 cases experience from a tertiary reference center in Turkey. Turk J Gastroenterol 2018; 29: 676-83.